Relationship between thrust, anthropometrics, and dry-land strength in a national junior swimming team - Morais, J. E.; Marques, M. C.; Rodríguez-Rosell, D.; Barbosa, T. M.; Marinho, D. A. (The Physician and Sportsmedicine, 2020)
Objectives: This study aimed to (i) assess an anthropometric and thrust inter-limb asymmetry, and; (ii) determine the contribution of anthropometrics, and dry-land upper-body strength and power to the thrust of talented adolescent swimmers.